2010
DOI: 10.1091/mbc.e10-02-0111
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleus-based Quality Control Mechanism for Cytosolic Proteins

Abstract: Mechanisms that monitor the folding states of polypeptides are found throughout the cell. In the cytosol, how misfolded proteins are recognized and degraded is poorly understood. Here, misfolded proteins are shown to traffic to the nucleus where they are ubiquitinated by the San1p E3 ubiquitin ligase and degraded by the 26S proteasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(231 citation statements)
references
References 59 publications
(96 reference statements)
10
220
1
Order By: Relevance
“…The hypothesis is in line with a study in yeast which showed that degradation of cytosolic misfolded carboxypeptidase Y (CPY*) occurs in the nucleus (Prasad et al, 2010). To understand if the cellular localization of the protein has an influence on its degradation, we measured the degradation kinetics of NES-FlucDM-EGFP in the nucleus, by performing a cycloheximide (CHX) chase experiment in the presence of an inhibitor of nuclear export.…”
Section: V456 Role Of the Nucleus In The Degradation Of Nes-flucdsupporting
confidence: 63%
See 2 more Smart Citations
“…The hypothesis is in line with a study in yeast which showed that degradation of cytosolic misfolded carboxypeptidase Y (CPY*) occurs in the nucleus (Prasad et al, 2010). To understand if the cellular localization of the protein has an influence on its degradation, we measured the degradation kinetics of NES-FlucDM-EGFP in the nucleus, by performing a cycloheximide (CHX) chase experiment in the presence of an inhibitor of nuclear export.…”
Section: V456 Role Of the Nucleus In The Degradation Of Nes-flucdsupporting
confidence: 63%
“…The results presented in Figure 47 as well as findings using CPY* in yeast (Prasad et al, 2010) suggest a model, where misfolded cytosolic proteins move to the nucleus for their degradation. This model would predict that some cellular factor can recognize these misfolded proteins in the cytosol and direct them to the nucleus for degradation.…”
Section: Flucdm-egfpmentioning
confidence: 56%
See 1 more Smart Citation
“…Through these non-invasive techniques, the localization of the proteasome in growing yeast and highly proliferating cancer cells has been elucidated to be primarily nuclear ( Enenkel et al , 1998; Laporte et al , 2008; McDonald & Byers, 1997; Russell et al , 1999). In line with this finding, increasing evidence in the literature suggests that certain misfolded proteins are imported from the cytoplasm into the nucleus solely for proteasomal degradation ( Park et al , 2013; Prasad et al , 2010). Conversely, transient nuclear proteins are exported into the cytoplasm for proteolysis, indicating a dynamic shift of proteasomal substrates between the nucleus and cytoplasm ( Chen & Madura, 2014a).…”
Section: Introductionmentioning
confidence: 63%
“…The latter, however, would imply that these proteins are actively imported as a result of the inhibition of their original function and thus were marked for protein degradation. Indeed, recent studies provide compelling evidence that cytosolic misfolded proteins are actively imported into the nucleus for proteasomal degradation (Prasad et al 2010;Park et al 2013;Shibata and Morimoto 2014). Having found that the major fraction of 20S proteasomes is located in nuclei of both placebo-and propiverinetreated F344 rats and that the BioGRID interaction database provides evidence that DAAO interacts with KLHL42, a substrate-specific adapter of an E3 ubiquitin-protein ligase, 1 we wanted to demonstrate that proteins, e.g., DAAO and catalase are imported into the nucleus for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%